Ідеологічні виміри російсько-української війни - Калініченко, Богдан Михайлович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
War is the extreme degree of conflict when the parties turn to military methods of confrontation. Almost all wars in the world take place for ideological reasons. Therefore, in order to find out the limits of the conflict, to predict the course and consequences of the confrontation, it is necessary to study its ideological component. At the moment, the ideological differences between Russia and Ukraine are so strong that the end of the war can be seen only in the return of Russia to the democratic path of development.